SRI TANJUNG: A NEW CREATION OF BALINESE DRAMA GONG - Suratni, Ni Wayan; Iriani, Ni Wayan; Desiari, Made Ayu (Journal of Innovation Research and Knowledge, 2024)
This applied research aims to create a new Balinese Drama Gong. Traditional Balinese Drama Gong is increasingly marginalized amidst the development of the entertainment industry. Only a few drama viewers know about the character Sri Tanjung in the Banyuwangi legend. The problems are: 1) What is the form of the new Balinese gong drama creation?; 2) What is the process of creating new Balinese Drama Gong?; A new Balinese Gong drama creation can be realized using R&D methods from an art studies perspective. The creation began with field study activities and a literature study regarding traditional Balinese Drama Gong and Banyuwangi legends. The output in the form of a formula is then constructed, implemented as a Balinese Drama Gong, tested, and promoted as a new creation of a Balinese Drama Gong. The results of the research show : 1) This new creation of Balinese Drama Gong uses the Sri Tanjung story, Gamelan Gong Kebyar, Indonesian language, sound system, fog, and modern lighting; 2) Sri Tanjung, a new creation of Balinese Drama Gong, was created through the make a scenario in the searching stage, the artwork designing stage, the socialization stage, the artwork testing stage, and the artwork promotion stage.